2023
DOI: 10.1371/journal.pone.0281104
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive retrospective study on HIV care cascade in a tertiary hospital in the Philippines

Abstract: Introduction The HIV care cascade is a model used to examine the engagement of people living with HIV (PLHIV) in medical care from the time of diagnosis to sustained viral suppression. This study describes the stages of the cascade from linkage to care, antiretroviral therapy (ART) initiation, retention in care, and virologic suppression- at the University of the Philippines—Philippine General Hospital (UP-PGH) STD/AIDS Guidance and Intervention Prevention (SAGIP) treatment hub in the context of existing casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A study on the care cascade of 3137 MSM diagnosed to have HIV in a community-based clinic in Manila showed a 98% viral suppression rate among 84% of PLHIV on ART who were tested for viral load [ 115 ]. In another surveillance study, an HIV clinic in a tertiary hospital found 95% viral suppression among the 48.2% of PLHIV on ART who had viral load testing [ 116 ].…”
Section: Viral Load Monitoring Genotyping and Resistance Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on the care cascade of 3137 MSM diagnosed to have HIV in a community-based clinic in Manila showed a 98% viral suppression rate among 84% of PLHIV on ART who were tested for viral load [ 115 ]. In another surveillance study, an HIV clinic in a tertiary hospital found 95% viral suppression among the 48.2% of PLHIV on ART who had viral load testing [ 116 ].…”
Section: Viral Load Monitoring Genotyping and Resistance Testingmentioning
confidence: 99%
“…HIV RNA viral load testing is unfortunately not routinely performed in the country due to the associated costs and limited availability [ 116 ]. An administrative order was issued by the DOH in 2022 to facilitate the integration of HIV and TB services.…”
Section: Viral Load Monitoring Genotyping and Resistance Testingmentioning
confidence: 99%